Analysis of Multiple Blockages in an Urban Drainage System: An Observational Study in the Simpang Elak Area, Aceh - Qanitatul Isra Qamal; Ramadhani R; Syahrul Gunawan; Afrilia Varisa; Salsabila Arnas Nasution5 (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The Simpang Elak area, Blang Mangat District, Lhokseumawe City, Aceh, is facing a chronic drainage crisis that disrupts its vital function as an alternative transportation route. The existing conventional drainage system has proven to be non-adaptive to local environmental characteristics and increasingly intense extreme rainfall patterns due to climate change, particularly problems caused by vegetation, waste, and soil that block nearly the entire drainage network. This study analyzes drainage system blockage issues in the Simpang Elak area, Blang Mangat, Lhokseumawe City, Aceh. The objective of the research is to identify the patterns, impacts, and mechanisms of multiple blockages that disrupt drainage performance. The method employed is direct field-based observational research conducted over eight weeks (November–December 2025) at five strategic observation points, focusing on documenting the types, locations, and frequency of blockages caused by vegetation, waste, and sedimentation. The results reveal three dominant blockage patterns: (1) invasive vegetation (particularly Pennisetum purpureum and Eichhornia crassipes) affecting 65% of observation points and reducing drainage capacity by 40–60%; (2) rapid accumulation of plastic waste at 85% of drainage inlets; and (3) soil and construction material sedimentation accumulating at a rate of 20–35 cm per month. The interaction of these three factors creates a synergistic effect that progressively exacerbates capacity reduction by up to 40–60% within 6–8 weeks, far exceeding the cumulative impact of each individual factor. This study concludes that the drainage system at the research site operates optimally for less than 25% of the conventional maintenance cycle (3–4 months). Reactive maintenance strategies and non-adaptive infrastructure design have been proven ineffective.